2011
DOI: 10.1016/j.jnucmat.2011.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemical reduction of solid uranium oxide in molten fluoride salts

Abstract: International audienceThe direct electrochemical reduction of UO2 solid pellets was carried out in LiF-CaF2 (+ 2 mass. % Li2O) at 850°C. An inert gold anode was used instead of the usual reactive sacrificial carbon anode. In this case, oxidation of oxide ions present in the melt yields O2 gas evolution on the anode. Electrochemical characterisations of UO2 pellets were performed by linear sweep voltammetry at 10mV/s and reduction waves associated to oxide direct reduction were observed at a potential 150mV mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Molten salts are unique solvent involved in many domains: 1 geoscience, energy (fuel cell, 2 nuclear energy, 3 battery, 4,5 solar technology 6,7,8 …), wastes treatment, materials synthesis, 9,10 metallurgy 11,12 … Molten fluorides main applications under development concern the nuclear energy in many aspects, 1,3 from the waste treatment 13,14,15 up to the molten salt nuclear reactor (one of the six reactor concepts of the Generation IV initiative). 16,17,18 Understanding and modelling their physical and chemical properties are crucial issues in such context.…”
Section: Introductionmentioning
confidence: 99%
“…Molten salts are unique solvent involved in many domains: 1 geoscience, energy (fuel cell, 2 nuclear energy, 3 battery, 4,5 solar technology 6,7,8 …), wastes treatment, materials synthesis, 9,10 metallurgy 11,12 … Molten fluorides main applications under development concern the nuclear energy in many aspects, 1,3 from the waste treatment 13,14,15 up to the molten salt nuclear reactor (one of the six reactor concepts of the Generation IV initiative). 16,17,18 Understanding and modelling their physical and chemical properties are crucial issues in such context.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of a sacrificial carbon anode has not been well tested. One of the major concerns with the sacrificial carbon anode is the formation of carbides due to the reduction of carbonates …”
Section: On‐line Purification Methodsmentioning
confidence: 99%
“…However, the use of a sacrificial carbon anode has not been well tested. One of the major concerns with the sacrificial carbon anode is the formation of carbides due to the reduction of carbonates . The other issue is that this type of impurity removal has not previously been implemented and detailed performance requirements for the sacrificial electrode have yet to be determined.…”
Section: Impurities Contamination Mechanisms and Available Removal mentioning
confidence: 99%
“…This result shows that huge cathode current begins at approximately ¹1.5 V vs. Pt; the cathodic limit corresponds to alkali-metal deposition. 23,27 When Li 2 CO 3 was added to the molten LiF-NaF, the cyclic voltammogram showed that an additional reduction current peak at approximately ¹1.4 V vs. Pt, as shown in Fig. 2.…”
Section: Cyclic and Squarewave Voltammetrymentioning
confidence: 96%